Skip to content
Related Articles

Related Articles

Improve Article
Save Article
Like Article

Class 11 RD Sharma Solutions – Chapter 29 Limits – Exercise 29.4 | Set 1

  • Last Updated : 28 Apr, 2021

Evaluates the following limits:

Question 1. Limx→0{√(1 + x + x2) – 1}/x.

Solution:

We have, Limx→0{√(1 + x + x2) – 1}/x

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12. 

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

Find the limit of the given equation when x =>0. 



When we put x = 0, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

Lim_{x→0}\frac{\sqrt{(1 + x + x^2)} - 1}{x}\times \frac{\sqrt{1 + x + x^2}+1}{\sqrt{1 + x + x^2}+1}

= Limx→0(1 + x + x2 – 1)/{x√(1 + x + x2) + 1}

= Limx→0{x(x + 1)}/{x√(1 + x + x2) + 1}

= Limx→0(x + 1)/{√(1 + x + x2) + 1}

Now put x = 0, we get

= (0 + 1)/{√(1 + 0 + 0) + 1}



= 1/2

Question 2. Limx→0(2x)/{√(a + x) – √(a – x)}

Solution:

We have, Limx→0(2x)/{√(a + x) – √(a – x)}

Find the limit of the given equation when x =>0. 

When we put x = 0, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

Lim_{x→0}\frac{(2x)}{\sqrt{a + x} - \sqrt{a - x}} \times \frac{\sqrt{a + x} + \sqrt{a - x}}{\sqrt{a + x} + \sqrt{a - x}}

= Limx→0[2x{√(a + x) + √(a – x)}]/{(a + x) – (a – x)}

= Limx→0[2x{√(a + x) + √(a – x)}]/2x

= Limx→0{√(a + x) + √(a – x)}



Now put x = 0, we get

= √a + √a

= 2√a

Question 3. Limx→0{√(a2 + x2) – a}/x2

Solution:

We have, Limx→0{√(a2 + x2) – a}/x2

Find the limit of the given equation when x =>0. 

When we put x = 0, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

Lim_{x→0}\frac{{\sqrt{(a^2 + x^2)} - a}}{x^2} \times \frac{\sqrt{(a^2 + x^2)} + a}{\sqrt{(a^2 + x^2)} + a}

= Limx→0(a2 + x2 – a2)/[x2{√(a2 + x2) + a}]



= Limx→0(x2)/[x2{√(a2 + x2) + a}]

= Limx→0(1)/{√(a2 + x2) + a}

Now put x = 0, we get

= 1/(a + a)

= 1/2a

Question 4. Limx→0{√(1 + x) – √(1 – x)}/2x

Solution:

We have, Limx→0{√(1 + x) – √(1 – x)}/2x

Find the limit of the given equation when x =>0. 

When we put x = 0, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

Lim_{x→0}\frac{\sqrt{(1 + x)} - \sqrt{(1 - x)}}{2x} \times \frac{\sqrt{(1 + x)} + \sqrt{(1 - x)}}{\sqrt{(1 + x)} + \sqrt{(1 - x)}}

= Limx→0(1 + x – 1 + x)/[2x{√(1 + x) + √(1 – x)}]

= Limx→0(2x)/[2x{√(1 + x) + √(1 – x)}]

= Limx→0(1)/{√(1 + x) + √(1 – x)}

Now put x = 0, we get

= 1/(1 + 1)

= 1/2

Question 5. Limx→2{√(3 – x) – 1}/(2 – x)

Solution:

We have, Limx→2{√(3 – x) – 1}/(2 – x)

Find the limit of the given equation



When we put x = 2, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

 Lim_{x→2}\frac{\sqrt{(3 - x)} - 1}{(2 - x)} \times \frac{\sqrt{(3 - x)} + 1}{\sqrt{(3 - x)} + 1}

= Limx→2{(3 – x) – 1}/[(2 – x){√(3 – x) + 1}]

= Limx→2(2 – x)/[(2 – x){√(3 – x) + 1}]

= Limx→2(1)/{√(3 – x) + 1}

Now put x = 2, we get

= 1/{√(3 – 2) + 1}

= 1/(1 + 1)

= 1/2

Question 6. Limx→3(x – 3)/{√(x – 2) – √(4 – x)}

Solution:

We have, Limx→3(x – 3)/{√(x – 2) – √(4 – x)}

Find the limit of the given equation

When we put x = 3, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

 Lim_{x→3}\frac{(x - 3)}{\sqrt{(x - 2)} - \sqrt{(4 - x)}} \times \frac{\sqrt{(x - 2)} + \sqrt{(4 - x)}}{\sqrt{(x - 2)} + \sqrt{(4 - x)}}

= Limx→3[(x – 3){√(x – 2) + √(4 – x)}]/{(x – 2) – (4 – x)}

= Limx→3[(x – 3){√(x – 2) + √(4 – x)}]/{2(x – 3)}

= Limx→3{√(x – 2) + √(4 – x)}/2

Now put x = 3, we get



= {√(3 – 2) + √(4 – 3)}/2

= (1 + 1)/2

= 1

Question 7. Limx→0(x)/{√(1 + x) – √(1 – x)}

Solution:

We have, Limx→0(x)/{√(1 + x) – √(1 – x)}

Find the limit of the given equation

When we put x = 0, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

Lim_{x→0}\frac{x}{\sqrt{(1 + x)} - \sqrt{(1 - x)}} \times \frac{\sqrt{(1 + x)} + \sqrt{(1 - x)}}{\sqrt{(1 + x)} + \sqrt{(1 - x)}}

= Limx→0[x{√(1 + x) + √(1 – x)}]/{(1 + x) – (1 – x)}

= Limx→0[x{√(1 + x) + √(1 – x)}]/(2x)

= Limx→0{√(1 + x) + √(1 – x)}/(2)

Now put x = 0, we get

= (√1 + √1)/2

= 2/2

= 1

Question 8. Limx→1{√(5x – 4) – √x}/(x – 1)

Solution:

We have, Limx→1{√(5x – 4) – √x}/(x – 1)

Find the limit of the given equation

When we put x = 1, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

 Lim_{x→1}\frac{\sqrt{(5x - 4)} - \sqrt{x}}{(x - 1)} \times \frac{\sqrt{(5x - 4)} + \sqrt{x}}{\sqrt{(5x - 4)} + \sqrt{x}}

= Limx→1{5x – 4 – x}/[(x – 1){√(5x – 4) + √x}]

= Limx→1{4(x – 1)}/[(x – 1){√(5x – 4) + √x}]

= Limx→1(4)/{√(5x – 4) + √x}

Now put x = 1, we get

= 4/{√(5 – 4) + √1}

= 4/(1 + 1)

= 2

Question 9. Limx→1(x – 1)/{√(x2 + 3) – 2}

Solution:



We have, Limx→1(x – 1)/{√(x2 + 3) – 2}

Find the limit of the given equation

When we put x = 1, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

Lim_{x→1}\frac{(x - 1)}{\sqrt{(x^2 + 3)} - 2} \times \frac{\sqrt{(x^2 + 3)} + 2}{\sqrt{(x^2 + 3)} + 2}

= Limx→1[(x – 1){√(x2 + 3) + 2}]/{(x2 + 3) – 4}

= Limx→1[(x – 1){√(x2 + 3) + 2}]/(x2 – 1)

= Limx→1[(x – 1){√(x2 + 3) + 2}]/{(x – 1)(x + 1)}

= Limx→1{√(x2 + 3) + 2}/{(x + 1)}

Now put x = 1, we get

= {√(1 + 3) + 2}/(1 + 1)

= (2 + 2)/2

= 2

Question 10.  Limx→3{√(x + 3) – √6}/(x2 – 9)

Solution:

We have, Limx→3{√(x + 3) – √6}/(x2 – 9)

Find the limit of the given equation

When we put x = 3, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

 Lim_{x→3}\frac{\sqrt{(x + 3)} - \sqrt{6}}{(x^2 - 9)} \times \frac{\sqrt{(x + 3)} + \sqrt{6}}{\sqrt{(x + 3)} + \sqrt{6}}

= Limx→3{(x + 3) – 6}/[(x2 – 9){√( x+ 3) + √6}]

= Limx→3(x – 3)/[(x – 3)(x + 3){√(x + 3) + √6}]

= Limx→3(1)/[(x + 3){√(x + 3) + √6}]

Now put x = 3, we get

\frac{1}{(3+3)(\sqrt6+\sqrt6)}

\frac{1}{(6)(2\sqrt6)}

= 1/(12√6)

Question 11. Limx→1{√(5x – 4) – √x}/(x2 – 1)

Solution:

We have, Limx→1{√(5x – 4) – √x}/(x2 – 1)

Find the limit of the given equation

When we put x = 1, this expression takes the form of 0/0.



So, on rationalizing the given equation we get

 Lim_{x→1}\frac{\sqrt{(5x - 4)} - \sqrt{x}}{(x^2 - 1)} \times \frac{\sqrt{(5x - 4)} + \sqrt{x}}{\sqrt{(5x - 4)} + \sqrt{x}}

= Limx→1{5x – 4 – x}/[(x2 – 1){√(5x – 4) + √x}]

= Limx→1{4(x – 1)}/[(x – 1)(x + 1){√(5x – 4) + √x}]

= Limx→1(4)/[{√(5x – 4) + √x}(x + 1)]

Now put x = 1, we get

= 4/[{√(5 – 4) + √1}(1 + 1)]

= 4/[(1 + 1)(1 + 1)]

= 4/4

= 1

Question 12. Limx→0{√(1 + x) – 1}/x

Solution:

We have, Limx→0{√(1 + x) – 1}/x

Find the limit of the given equation

When we put x = 0, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

Lim_{x→0}\frac{\sqrt{(1 + x)} - 1}{x} \times \frac{\sqrt{(1 + x)} + 1}{\sqrt{(1 + x)} + 1}

= Limx→0(1 + x – 1)/[x{√(1 + x) + 1}]

= Limx→0(x)/[x{√(1 + x) + 1}]

= Limx→0(1)/{√(1 + x) + 1}

Now put x = 0, we get

= 1/(1 + 1)

= 1/2

Question 13. Limx→2{√(x2 + 1) – √5}/(x – 2)

Solution:

We have, Limx→2{√(x2 + 1) – √5}/(x – 2)

Find the limit of the given equation

When we put x = 2, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

 Lim_{x→2}\frac{\sqrt{(x^2 + 1)} - \sqrt{5}}{(x - 2)} \times \frac{\sqrt{(x^2 + 1)} + \sqrt{5}}{\sqrt{(x^2 + 1)} + \sqrt{5}}

= Limx→2{x2 + 1 – 5}/[(x – 2){√(x2 + 1) + √5}]

= Limx→2{(x2 – 4)}/[(x – 2){√(x2 + 1) + √5}]



= Limx→2{(x – 2)(x + 2)}/[(x – 2){√(x2 + 1) + √5}]

= Limx→2{(x + 2)}/{√(x2 + 1) + √5}

Now put x = 2, we get

= 4/{√(5) + √5}

= 4/(2√5)

= 2/(√5)

Question 14. Limx→2(x – 2)/{√x – √2}

Solution:

We have, Limx→2(x – 2)/{√x – √2}

Find the limit of the given equation

When we put x = 2, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

Lim_{x→2}\frac{(x - 2)}{√x - √2} \times \frac{√x + √2}{√x + √2}

= Limx→2[(x – 2){√x + √2}]/{x – 2}

= Limx→2{√x + √2}

Now put x = 2, we get

= √2 + √2

= 2√2

Question 15. Limx→7{4 – √(9 + x)}/{1 – √(8 – x)}

Solution:

We have, Limx→7{4 – √(9 + x)}/{1 – √(8 – x)}

Find the limit of the given equation

When we put x = 7, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

=\lim_{x\to7}\frac{(4-\sqrt{9+x})(4+\sqrt{9+x})(1+\sqrt{8-x})}{(1-\sqrt{8-x})(4+\sqrt{9+x})(1+\sqrt{8-x})}

=\lim_{x\to7}\frac{16-(9+x)}{1-(8-x)}×\frac{(1+\sqrt{8-x})}{(4+\sqrt{9+x})}

=\lim_{x\to7}\frac{(7-x)}{-1(7-x)}×\frac{(1+\sqrt{8-x})}{(4+\sqrt{9+x})}

Now put x = 7, we get

= -{1 + √(8 – 7)}/{4 + √(9 + 7)}

= -2/(4 + 4)

= -1/4

Question 16. Limx→0{√(a + x) – √a}/[x{√(a2 + ax)}]

Solution:



We have,

Limx→0{√(a + x) – √a}/[x{√(a2 + ax)}]

Find the limit of the given equation

When we put x = 0, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

Lim_{x→0}\frac{\sqrt{(a + x)} - \sqrt{a}}{x\sqrt{(a^2 + ax)}} \times \frac{\sqrt{(a + x)} + \sqrt{a}}{\sqrt{(a + x)} + \sqrt{a}}

= Limx→0{(a + x) – a}/[x{√(a2 + ax)}{√(a + x) + √a}]

= Limx→0(x)/[x{√(a2 + ax)}{√(a + x) + √a}]

= Limx→0(1)/[{√(a2 + ax)}{√(a + x) + √a}]

Now put x = 0, we get

= 1/{a.(√a + √a)}

= 1/(2a√a)

Question 17. Limx→7(x – 5)/{√(6x – 5) – √(4x + 5)}

Solution:

We have, Limx→7(x – 5)/{√(6x – 5) – √(4x + 5)}

Find the limit of the given equation

When we put x = 7, this expression takes the form of 0/0.

So, on rationalizing the given equation we get

 Lim_{x→7}\frac{(x - 5)}{\sqrt{(6x - 5)} - \sqrt{(4x + 5)}} \times \frac{\sqrt{(6x - 5)} + \sqrt{(4x + 5)}}{\sqrt{(6x - 5)} + \sqrt{(4x + 5)}}

= Limx→7[{√(6x – 5) + √(4x + 5)}(x – 5)]/{(6x-5) – (4x + 5)}

= Limx→7[{√(6x – 5) + √(4x + 5)}(x – 5)]/{2(x – 5)}

= Limx→7[{√(6x – 5) + √(4x + 5)}]/(2)

Now put x = 7, we get

= {√(6 × 7 – 5) + √(4 × 7 + 5)}/(2)

= (5 + 5)/2

= 5




My Personal Notes arrow_drop_up
Recommended Articles
Page :